The determining factors of tourist satisfaction using airasia as a preferred airline to travel to the domestic destination - Farah Ismanazihah Rosli; Fariza Suhada Sulawizi; Farrah Adillah Jefree; Fatin Aisyah Hanani Obet (2023)
Air Asia Airline is Asia’s leading low-cost airline. The purpose of the study is to determine the effect of service quality, motivation, involvement on tourist satisfaction to travel to domestic destinations. The objective of this study is to see if there is a link between service quality, motivation, involvement and tourist satisfaction using Air Asia as a preferred airline to travel to domestic destinations. This study used a quantitative survey of tourists who use Air Asia as an airline to travel and used the Statistical Package for Social Sciences (SPSS) to collect the data of respondents. A total of 306 respondents participated to answer all questions in this survey. Service quality, motivation and involvement have significant relationships with tourist satisfaction. So, all the hypotheses are supported. Therefore, this study helps Air Asia to improve service quality especially on time management and motivates and encourages involvement of passengers to use Air Asia. Thus, it brings satisfaction to all passengers. Keywords: Air Asia, Tourist, Service Quality, Motivation, Involvement and Tourist Satisfaction.